2013
DOI: 10.7598/cst2013.438
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Growth and Characterization of 1-(2,4-Dichlorophenyl-2yl)-3-(4-hydroxyphenyl)prop-2-en-1-one

Abstract: A potential crystal for nonlinear optical application and monomer namely 1-(2,4-dichlorophenyl-2yl)-3-(4-hydroxyphenyl)prop-2-en-1-one (DHPP) was synthesized and grown by slow evaporation technique. The functional groups present in the compound were identified by FTIR spectrum. The optical cutoff wavelength and structural characteristics were analyzed using UV-Vis-NIR spectra and single crystal x-ray diffractometer. The crystal belongs to non centrosymmetric orthorhombic system with space group Pna21 with cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Moreover, these types of compounds can easily be grown into bulk crystals using cheap organic solvents at ambient conditions. Most of the chalcone derivatives have good transparency and oxidative stability 8,9 . Recently, we found that presence of bromo substituent and sulfur atom especially in the form of thiophene ring is useful in getting good quality single crystals 5,6 .…”
mentioning
confidence: 99%
“…Moreover, these types of compounds can easily be grown into bulk crystals using cheap organic solvents at ambient conditions. Most of the chalcone derivatives have good transparency and oxidative stability 8,9 . Recently, we found that presence of bromo substituent and sulfur atom especially in the form of thiophene ring is useful in getting good quality single crystals 5,6 .…”
mentioning
confidence: 99%
“…By varying the phenolic structure with suitable substituents, it is possible to fine tune the polymer structure with unique properties required for specific applications [2][3][4][5][6][7][8][9] . Chalcones are a class of compounds mostly studied for pharmacological properties 10,11 and recently have been explored for their optical applications [12][13][14][15] . In the past few years chalcones have been shown to possess interesting biological properties like anti-invasive 16 , anticancer 17,18 , antimalarial 19 , antimicrobial 20 , antimutagenic 21 , radioprotective 22 , anti-inflammatory effects 23 and find use as synthetic intermediates 24 .…”
Section: Introductionmentioning
confidence: 99%